2020
DOI: 10.1073/pnas.2009539118
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin controls proximodistal blastema polarity in zebrafish fin regeneration

Abstract: Planarian flatworms regenerate their heads and tails from anterior or posterior wounds and this regenerative blastema polarity is controlled by Wnt/β-catenin signaling. It is well known that a regeneration blastema of appendages of vertebrates such as fish and amphibians grows distally. However, it remains unclear whether a regeneration blastema in vertebrate appendages can grow proximally. Here, we show that a regeneration blastema in zebrafish fins can grow proximally along the proximodistal axis by calcineu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 40 publications
1
31
1
Order By: Relevance
“…In contrast to our results, a recent report by Cao et al [ 26 ] on fin hole regeneration did not mention the expression of regeneration-related genes at the distal margin of the hole. This is possibly due to the differences in experimental conditions; in their report, two fin ray rows were excised, but we excised one row.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our results, a recent report by Cao et al [ 26 ] on fin hole regeneration did not mention the expression of regeneration-related genes at the distal margin of the hole. This is possibly due to the differences in experimental conditions; in their report, two fin ray rows were excised, but we excised one row.…”
Section: Discussioncontrasting
confidence: 99%
“…This is possibly due to the differences in experimental conditions; in their report, two fin ray rows were excised, but we excised one row. In addition, the length of the hole prepared in our study was longer than that in their experiment [ 26 ]. Because the area of gene expression in the distal margin was restricted to a small area in our experiment, as mentioned above, the signals of gene expression may be unclear in other experimental conditions.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A recent finding showed that calcineurin inhibition or increased activity of the voltagegated Kcnh2 channel (lof mutant) promotes regenerative outgrowth from the proximal side of a mid-fin excavation, a site that normally does not mount a regenerative outgrowth response (Cao et al, 2021). Our findings help explain how calcineurin-regulated and electrophysiological changes from potassium channels can lead to broader tissue organizing phenomena by showing the inductive effect that increasing K + conductance (and calcineurin's regulation of K + conductance) can have on a broad number of developmental pathways, which is important for coordinating the organized formation of tissues and organs.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish ( Danio rerio ) has remarkable regenerative capabilities and becomes one of the most widely used vertebrate models for regenerative studies. Zebrafish is capable of regenerating a range of tissues including fin ( Shibata et al, 2016 ; Cao et al, 2021 ), heart ( Poss et al, 2002 ), spinal cord ( Mokalled et al, 2016 ), brain ( Lucini et al, 2018 ), liver ( He et al, 2014 ), hair cells ( Thomas and Raible, 2019 ), kidney ( Reimschuessel, 2001 ), and retina ( Vihtelic and Hyde, 2000 ). Although regeneration studies mainly focus on these somatic tissues, recent studies about reproductive system regeneration attract much interest.…”
Section: Introductionmentioning
confidence: 99%